2020
DOI: 10.1155/2020/2903861
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Characterization and Analysis of bHLH Transcription Factors Related to Crocin Biosynthesis in Gardenia jasminoides Ellis (Rubiaceae)

Abstract: Crocins, enriched in Gardenia jasminoides fruits, have a pharmacological activity against central nervous system diseases, cardiovascular diseases, and cancer cell growth. The biosynthesis of crocins has been widely explored, but its regulatory mechanism remains unknown. Here, the basic helix-loop-helix (bHLH) transcription factors related to crocin biosynthesis were systematically identified on the basis of the genome of G. jasminoides. A total of 95 GjbHLH transcription factor genes were identified, and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…The bHLH TFs participate in various biological processes, such as plant fertility [23]; anthocyanin accumulation [24]; leaf senescence [25]; and responses to biotic and abiotic stresses [26]. Although the bHLH gene family has been widely identified in different plant species, such as 147 bHLHs in Arabidopsis [27], 183, 231 and 571 bHLHs in rice, maize and wheat, respectively [28], 94 VvbHLHs in grape [29], 95 GjbHLHs in Gardenia jasminoides [30], and 85 GbbHLHs in Ginkgo biloba [31], the genome-wide identification of the MYC gene family is limited, including 27 TaMYCs in wheat (Chinese Spring) [19]; 26 TaMYCs in the wheat genome [32]; and 23 SsMYCs in Saccharum spontaneum [20]. Here, 32 HblMYCs were genome-wide identified in the rubber tree.…”
Section: Discussionmentioning
confidence: 99%
“…The bHLH TFs participate in various biological processes, such as plant fertility [23]; anthocyanin accumulation [24]; leaf senescence [25]; and responses to biotic and abiotic stresses [26]. Although the bHLH gene family has been widely identified in different plant species, such as 147 bHLHs in Arabidopsis [27], 183, 231 and 571 bHLHs in rice, maize and wheat, respectively [28], 94 VvbHLHs in grape [29], 95 GjbHLHs in Gardenia jasminoides [30], and 85 GbbHLHs in Ginkgo biloba [31], the genome-wide identification of the MYC gene family is limited, including 27 TaMYCs in wheat (Chinese Spring) [19]; 26 TaMYCs in the wheat genome [32]; and 23 SsMYCs in Saccharum spontaneum [20]. Here, 32 HblMYCs were genome-wide identified in the rubber tree.…”
Section: Discussionmentioning
confidence: 99%
“…QRT-PCR analysis showed that BcbHLH57 was upregulated at low and high temperatures at 24 h. These results suggest that bHLH57 mediate the physiological regulation process of hormone regulation against abiotic stress in wucai. BHLH57 was an important gene involved in seed germination and is involved in ABA mediate regulation of seed dormancy (Tian et al 2020). BHLH57 positively regulate seed dormancy by inducing the expression of genes encoding ABA biological synthase (NCED6 and NCED9) (Alam et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The C-terminal HLH domain contributes to the specificity of transcriptional regulation in eukaryotes [ 14 ]. So far, various numbers of bHLH TFs have been identified in different species, including 162 in Arabidopsis thaliana , 183 in Populus trichocarpa , 197 in Pyrus bretschneideri , 115 in Vitis davidii , 91 in Liriodendron chinense , 134 in Camellia sinensis , 118 in Ficus carica , and 95 in Gardenia jasminoides , respectively [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Most bHLH TF family studies focus on anthocyanin biosynthesis.…”
Section: Introductionmentioning
confidence: 99%